2020
DOI: 10.1192/bjo.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term (saliva) and long-term (hair) cortisol levels in out-patients with melancholic and non-melancholic major depression

Abstract: Background Major depressive episodes (MDEs) show diverse cortisol level alterations. Heterogeneity in symptom profiles, symptom severity and cortisol specimens may explain these heterogeneous results. Less severely ill out-patients with a non-melancholic MDE (NM-MDE) may have a variation in the rhythm of cortisol secretion rather than in its concentration. Method Cortisol measures were taken (a) over a short-term period (12 h) by measuring daily salivary output using the area under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In all cases, experiencing greater levels of early or recent life stress increased levels of suspiciousness specifically in those presenting elevated HCC. These findings are consistent with previous evidence linking childhood trauma as well as recent stress with the HPA axis function, psychiatric illness in general ( Murphy et al, 2022 ) and psychosis in particular ( Faravelli et al, 2017 ; Aas et al, 2019 ; Herane-Vives et al, 2020 ). More so, results provide further support for the neural diathesis-stress model ( Walker et al, 2008 ) and extend findings to nonclinical expressions of psychosis liability.…”
Section: Discussionsupporting
confidence: 92%
“…In all cases, experiencing greater levels of early or recent life stress increased levels of suspiciousness specifically in those presenting elevated HCC. These findings are consistent with previous evidence linking childhood trauma as well as recent stress with the HPA axis function, psychiatric illness in general ( Murphy et al, 2022 ) and psychosis in particular ( Faravelli et al, 2017 ; Aas et al, 2019 ; Herane-Vives et al, 2020 ). More so, results provide further support for the neural diathesis-stress model ( Walker et al, 2008 ) and extend findings to nonclinical expressions of psychosis liability.…”
Section: Discussionsupporting
confidence: 92%
“…It must be stated that the temporality between cortisol dysregulation and psychological manifestation remains largely misunderstood and may take longer than three months to associate fully. However, other teams also reported no prediction of depressive symptoms through hair cortisol levels ( Dowlati et al, 2010 , Gerritsen et al, 2019 , Herane-Vives et al, 2020a , Herane-Vives et al, 2018 , Herane-Vives et al, 2020b , Herane-Vives et al, 2020c , Kuehl et al, 2015 , Mayer et al, 2018 , Psarraki et al, 2021 , Steudte-Schmiedgen et al, 2017 ). Another explanation for the absence of association between cortisol change and PTSD, anxiety, and depression can be that cortisol may not be an important pathophysiological mechanism underlying these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, when examining the long-term activity of the HPA axis assessing HCC in depressed patients, results are unclear. A recent meta-analysis by Psarraki and colleagues (10) shows that most studies found no significant differences in HCC between Major Depression Disorder (MDD) patients and controls (11)(12)(13), although one study (14) showed higher HCC and two studies (15,16) found lower HCC in MDD patients. Nonetheless, higher levels of HCC were found in first episode compared to recurrent depression (17,18) or when there is comorbidity between MDD and an anxiety disorder (19).…”
Section: Introductionmentioning
confidence: 99%